The craft of research - Booth, Wayne C.; Colomb, Gregory G.; Williams, Joseph M. (Chicago : University of Chicago Press, 2008)
This book is a resource for researchers at every level, from first-year undergraduates to research reporters at corporations and government offices. Seasoned researchers and educators, the authors present an updated third edition of their classic handbook which explains how to build an argument that motivates readers to accept a claim; how to anticipate the reservations of readers and to respond to them appropriately; and how to create introductions and conclusions that answer that most demanding question, "So what?". It includes an expanded discussion of the essential early stages of a research task: planning and drafting a paper. The authors have revised and fully updated their section on electronic research, emphasizing the need to distinguish between trustworthy sources (such as those found in libraries) and less reliable sources found with a quick Web search. A chapter on warrants has also been thoroughly reviewed to make this difficult subject easier for researchers. Throughout, the authors have preserved the amiable tone, the reliable voice, and the sense of directness that have made this book indispensable for anyone undertaking a research project.
pt. 1. Research, researchers, and readers -- Prologue: Becoming a researcher -- Thinking in print: the uses of research, public and private -- Connecting with your reader: (re- )creating yourself and your readers -- pt. 2. Asking questions, finding answers -- Prologue: Planning your project : an overview -- From topics to questions -- From questions to a problem -- From problems to sources -- Engaging sources -- pt. 3. Making a claim and supporting it -- Prologue: Assembling a research argument -- Making good arguments: an overview -- Making claims -- Assembling reasons and evidence -- Acknowledgments and responses -- Warrants -- pt. 4. Planning, drafting, and revising -- Prologue: Planning again -- Planning -- Drafting your report -- Revising your organization and argument -- Communicating evidence visually -- Introductions and conclusions -- Revising style: telling your story clearly -- pt. 5. Some last considerations.
Includes bibliographical references and index.
Research, researchers, and readers -- Prologue: Becoming a researcher -- Thinking in print: Uses of research, public and private -- Connecting with your reader: (Re- )creating yourself and your audience -- Asking questions, finding answers -- Prologue: Planning your project - an overview -- From topics to questions -- From questions to a problem -- From problems to sources -- Engaging sources -- Making a claim and supporting it -- Prologue: Assembling a research argument -- Making good arguments: Overview -- Making claims -- Assembling reasons and evidence -- Acknowledgments and responses -- Warrants -- Planning, drafting, and revising -- Prologue: Planning again -- Planning -- Drafting your report -- Revising your organization and argument -- Communicating evidence visually -- Introductions and conclusions-- Revising style: Telling your story clearly -- Some last considerations.
Keywords: Research -- Methodology; Technical writing; Research -- Methodology; Technical writing; Research -- Methodology; Technical writing; Research -- Methodology; Technical writing